Avaliação do perfil imunorreativo de peptídeos recombinantes selecionados por Phage Display contra IgG humana de pacientes com a doença de Chagas crônica - Messias, Flávia Figueira (2010)
Chagas disease, an American trypanosomiasis caused by Trypanosoma cruzi, was discovered by Carlos Chagas in 1909, and presents a broad spectrum of clinical manifestations, including the acute and chronic phases. The latter is divided into three main forms: digestive, cardiac and indeterminate. The purposes of this study were to evaluate the immunoreactivity profile of recombinant peptides selected against purified human IgG from chronic chagas disease patients by Phage Display, to assess differential recognition patterns in the immune response among disease clinical forms, and to select mimotopes with potential use in diagnostics. The enzyme-linked immunosorbent assay (ELISA) was conducted with all 50 clones obtained after four rounds of selection. The trials were performed with phages supernatant. In order to evaluate the specific antibody response, plaque reduction tests were performed with clones that showed better performance in ELISAs. ELISA tests showed that the immune profile of some clones suggested the tendency of patients with the indeterminate form to develop cardiac or digestive form. Phage display approach has generated specific mimotopes that present differential recognition patterns of the immune response between the cardiac and digestive clinical forms of Chagas disease, and these mimotopes may become potential targets for vaccine development and for differential diagnostics of clinical forms.